Adenosine receptors on the immuno-oncology expressway: TIME, perspectives, and translation - Majumder, Biswanath; Datta, Santanu (Frontiers in Immunology, 2026)
A decade since immune checkpoint inhibitors made a stride in the clinical landscape of oncology, there has been a substantial focus on understanding the response heterogeneity following these therapies. Insights gained from clinical data identified the primary and secondary resistance mechanisms that escape the upfront therapy pressure. Beyond PD-1 and CTLA-4, new checkpoints averting this pressure are under clinical development. Adenosinergic pathways are actively engaged in oncogenic signaling. The main protagonists, CD73, A2AR, and A2BR, span diverse immune subsets of lymphoid and myeloid lineages and have emerged as alternative checkpoints. This review discusses the latest update on immune regulation dynamics of adenosine receptor signaling and their complex interplay with hypoxia in a heterogeneous tumor immune microenvironment (TIME). In this spectrum, we also review the plasticity of A2AR and A2BR in designing new drug candidates, tracing their complex metabolic roots in inducing immune dysfunction. Beyond the existing modalities, the ENT1 and MTAP-loss-MTA axis shows scope for alternative perturbations. The CD39-CD73-A2AR axis plays a central role in the terminal exhaustion of T cells. We highlight the interventions that disrupt the mechanistic context of A2AR and its cooperativity with other suppressors to restore anti-tumor immune functions following inhibition of their multilayered signaling. We capture the ongoing clinical trials and predictive biomarker landscape, along with novel delivery methods, to illustrate the evolving trends in this field. From these perspectives, we discuss how the adenosine axis can widen this new therapeutic avenue and boost the efficacy of CAR-T therapies. Therapeutic cancer vaccines are a new modality in this premise. Finally, an integrated overview of this pathway, along with TIME dynamics, illustrates the barriers and opportunities of combining adenosine signaling inhibitors in clinical trials.